Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/np4008427
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of Humulone Autoxidation Products and Analysis of Their Occurrence in Stored Hops

Abstract: The transformation of α-acids [in hops (Humulus lupulus L.)] to iso-α-acids (in beer) during the brewing process is well known, but the occurrence and structure of the oxidized α-acids during hop storage are not well documented. Because an understanding of these oxidized compounds is essential to optimize the effects of oxidized hops on the quality of beer, we investigated the autoxidation products of humulone (a representative congener of α-acids) using a simplified autoxidation model. Among the oxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…In contrast, oxidation of α-and β-acids produces bitter acid oxides, such as matured hop bitter acids (MHBA). All of the structurally elucidated compounds of MHBA possess a common β-tricarbonyl moiety similar to α-, β-, and isoα-acids (Taniguchi et al, 2013(Taniguchi et al, , 2014a(Taniguchi et al, , 2014b(Taniguchi et al, , 2015. We demonstrated that MHBA suppresses diet-induced body fat accumulation in animals (Morimoto-Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, oxidation of α-and β-acids produces bitter acid oxides, such as matured hop bitter acids (MHBA). All of the structurally elucidated compounds of MHBA possess a common β-tricarbonyl moiety similar to α-, β-, and isoα-acids (Taniguchi et al, 2013(Taniguchi et al, , 2014a(Taniguchi et al, , 2014b(Taniguchi et al, , 2015. We demonstrated that MHBA suppresses diet-induced body fat accumulation in animals (Morimoto-Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 76%
“…The obtained respective solid was dissolved in EtOH (0.500 mg/mL) and analyzed by a Prominence UFLC system (Shimadzu, Kyoto, Japan). The analyses were performed using the following conditions 32,33) : column: 100 × 2.1 mm id, 3 μm, Alltima C 18 column (Systech, Tokyo, Japan); solvent: H 2 O/H 3 PO 4 (85%), 1000/0.2, (v/v) containing EDTA (0.02% w/v) (solvent A) and MeCN (solvent B), a linear gradient from 10 to 52% B in 0 → 26.7 min, 52% B for 26.7 → 30 min, 52 to 75% B in 30 → 32.7 min, 75 to 85% B in 32.7 → 36.7 min, and 85% B for 36.7 → 37.7 min; flow rate: 0.6 mL/min; detector: 270 nm; and column temperature: 40°C. The injection volume was 3.0 μL.…”
Section: Methodsmentioning
confidence: 99%
“…1). 32,33) We also revealed that 4′-hydroxyallohumulinones (6a-c) isomerize into 4′-hydroxyallo-cis-humulinones (7a-c) and degrade into cis-oxyhumulinic acids (8a-c) during the wort boiling process (Fig. 1).…”
mentioning
confidence: 88%
“…Ještě menší je pokles obsahu beta kyselin (8,3 % rel.). Je to dáno tím, že řada transformačních reakcí alfa kyselin, na rozdíl od beta kyselin, nevyžaduje přítomnost kyslíku (Taniguchi, 2014). Skladování granulovaného chmele za přístupu vzduchu při teplotách kolem 20 °C má na kvalitu chmele silně destruktivní vliv.…”
Section: Hořké Látky a Stáří Chmeleunclassified
“…Even lower is the decrease in beta acid content (8.3% rel.). This is due to the fact that unlike in beta acids, a number of transformation reactions of alpha acids do not require the presence of oxygen (Taniguchi, 2014). Storage of granulated hop in air at temperatures around 20 °C has a strong destructive effect on the quality of hops.…”
Section: Vliv Ročníku Na Obsah Hořkých Látek Ve Chmelumentioning
confidence: 99%